Encouraging people to be more open-minded about counterattitudinal messages - Banks, Lane M. (Kansas State University, 2022)
Selective exposure is a problematic behavior that can have detrimental effects within various domains, such as health, learning, and decision-making. In an attempt to address this selective exposure problem, this study focused on addressing three maladaptive tendencies regarding people’s reception to counterattitudinal messages: 1) jumping to negative conclusions about the source from the recipient’s attitudes of the message, 2) jumping to negative conclusions about the quality of a message from the position it advocates without reviewing the quality of the arguments, and 3) avoiding exposure to arguments supporting the other side of an issue counter to what the recipient believes. Based on theory, three different techniques, all relying on some aspect of personal relevance, were tested and compared to investigate which would influence participants to be more open-minded about counterattitudinal messages. The personal attack processing frame asked the participants to not derogate the source. The idea attack processing frame asked the participants to not derogate the message. The third persuasive appeal, the unable to defend position processing frame, informed participants of the benefits of being familiar with points from the other side of an issue. Participants read a counterattitudinal message about increasing internet service taxes. After reading the message participants rated the source, the message, and their own engagement level. The three messages were compared to an irrelevant-frame control. Analyses indicated that no one message was more effective at persuading people across these dimensions. In fact, the personal attack frame was particularly ineffective. However, the unable to defend position frame influenced participants to pay more attention, put more thought into reading the message, and be more open-minded. This suggests that people are motivated to engage more with a counterattitudinal message when they are reminded of a time in which they were vulnerable due to a lack of knowledge.
Keywords: Selective exposure; Congruity theory